Physical structure determines compression of membrane biofilms during Gravity Driven Membrane (GDM) ultrafiltration. (15th October 2018) - Desmond, Peter; Morgenroth, Eberhard; Derlon, Nicolas
Abstract: Increasing transmembrane pressure (TMP) can compress and increase the hydraulic resistance of membrane biofilms. The purpose of the present study is to evaluate how compression of membrane biofilms occurs and how structural rearrangement can affect hydraulic resistance. Biofilms with heterogeneous and homogeneous physical structures were grown in membrane fouling simulators (MFS) in dead-end mode for 20 days with either (i) a nutrient enriched condition with a nutrient ratio of 100:30:10 (C: N: P), (ii) a phosphorus limitation (C: N: P ratio: 100:30:0), or (iii) river water (C: N: P ratio: ca. 100:10:1). The structural and hydraulic response of membrane biofilms to (a) changes in transmembrane pressures ( 0.06-0.1-0.5-0.1-0. 06 bar) and (b) changes in permeate flux ( 10-15-20-15- 10 L/m 2 /h) were investigated. Optical coherence tomography (OCT) was used to monitor biofilm structural response, and OCT images were processed to quantify changes in the mean biofilm thickness and relative roughness. Nutrient enriched and river water biofilms had heterogeneous physical structures with greater surface roughness (Ra' > 0.2) than homogeneous P limiting biofilms (Ra' < 0.2). Compression of biofilms with rough heterogeneous structures (Ra' > 0.2) was irreversible, indicated by irreversible decrease in surface roughness, partial relaxation in mean biofilm thickness and irreversible increase in hydraulic resistance. Compression of homogeneous biofilm (Ra' < 0.2) was on the other hand reversible, indicated by full relaxation of the biofilms structure and restoration of initial hydraulic resistance. Hydraulic response (i.e., change in the specific biofilm resistance) did not correspond with the change in physical structure of heterogeneous biofilms. The presented study provides a fundamental understanding of how biofilm physical structure can affect the biofilm's response to a change in TMP, with practical relevance for the operation of GDM filtration systems. Highlights: Initial morphology determines biofilm physical compression. Heterogeneous biofilms are irreversibly compressed. Homogeneous biofilms are reversibly compressed. Physical compression of biofilms on membranes increases hydraulic resistance. Increase in hydraulic resistance is not directly coupled to physical compression.